(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents a comprehensive framework for redesigning oil and gas engineering education through a competency-oriented, staged approach. The proposed model employs a three-tier system (A–Foundational, B–Intermediate, C–Advanced) with six sub-levels (A1–C2) aligned with Bloom’s taxonomy and international accreditation standards. The framework integrates competency mapping as a unifying instrument that coordinates curriculum design, learning outcomes, assessment strategies, and continuous quality improvement. Grounded in outcomes-based education (OBE) principles and the Conceive-Design-Implement-Operate (CDIO) framework, this approach bridges the gap between academic preparation and industry requirements by incorporating standards from the American Petroleum Institute (API), International Organization for Standardization (ISO 14001), Health, Safety, and Environment (HSE) protocols, and Project Management Body of Knowledge (PMBOK). The competency typology encompasses four domains: Universal Human Competencies (UHC), Universal Professional Competencies (UPC), Domain-Specific Professional Competencies (PC,) Self-Development Competencies (SDC), assessed through Knowledge-Skills-Attitude (K-S-A) models. Implementation strategies include diagnostic testing, rubric-based assessment, authentic project-based learning, and individualized learning pathways. The framework aims to produce graduates with robust technical competencies, digital fluency, ecological responsibility, and readiness for industry practice or entrepreneurial ventures.